Interaction of leisure‐time physical activity with body mass index on the risk of obesity‐related cancers: A pooled study. Issue 6 (7th April 2022) - Sun, Ming; Bjørge, Tone; Teleka, Stanley; Engeland, Anders; Wennberg, Patrik; Häggström, Christel; Stocks, Tanja
Abstract: Physical activity (PA) has been associated with a lower risk of some obesity‐related cancers, but the combined association and interaction of PA and body weight on obesity‐related cancer risk is less clear. We examined the association of leisure‐time PA (high/low) and its combination with body mass index (BMI, <25 [low]/≥25 [high] kg/m 2 ) on obesity‐related cancer risk in 570 021 individuals, aged 43 years on average at baseline, in five Scandinavian cohorts. We used Cox regression to calculate hazard ratios of obesity‐related cancers (n = 19 074) and assessed multiplicative and additive interactions between PA and BMI on risk. High leisure‐time PA, recorded in 19% of the individuals, was associated with a 7% (95% confidence interval [CI] 4%‐10%) lower risk of any obesity‐related cancer compared to low PA, with similar associations amongst individuals with a low and a high BMI (6% [1%‐11%] and 7% [2%‐11%]). High PA was also associated with decreased risks of renal cell (11% [9%‐31%]) and colon cancer (9% [2%‐16%]). When high PA and low BMI were combined, the relative risk reduction for all obesity‐related cancers was 24% (95% CI 20%‐28%); endometrial cancer, 47% (35%‐57%); renal cell cancer, 39% (27%‐51%); colon cancer, 27% (19%‐35%); multiple myeloma, 23% (2%‐40%) and pancreatic cancer, 21% (4%‐35%), compared to low PA‐high BMI. There were no additive or multiplicative interactions between PA and BMI on risk. The result of our study suggests a reduced risk of obesity‐related cancer by leisure‐time PA in both normal weight and overweight individuals, which further decreased for PA and normal weight combined. Abstract : What's new? Evidence suggests that physical activity lowers risk of certain obesity‐related cancers. Whether physical activity and body weight act together to prevent cancer, however, remains unclear. In this study, the authors explored the impact on obesity‐related cancer risk of associations and interactions between physical activity and body mass index (BMI). While high leisure‐time physical activity and normal weight were individually associated with reduced obesity‐related cancer risk, the greatest risk reduction occurred in the presence of both high physical activity and normal weight. No additive or multiplicative interactions were observed. The findings highlight the importance of physical activity in obesity‐related cancer prevention.